Malawi Economic Monitor, November 2017 : Land for Inclusive Development - Kandoole, Priscilla (World Bank, Washington, DC, 2017)
The Malawi Economic Monitor (MEM) provides an analysis of economic and structural development issues in Malawi. The aim of the publication is to foster better-informed policy analysis and debate regarding the key challenges that Malawi faces in its endeavor to achieve high rates of stable, inclusive, and sustainable economic growth. Malawi’s economy is primarily based on agriculture and heavily reliant on its land resources to achieve social and economic development. The recently promulgated land acts have the potential to create multiple economic and social benefits for Malawi's citizens by improving investor confidence in the business environment, reducing the cost of documenting rights, supporting decentralization, improving land use planning, and protecting vulnerable groups’ land rights and livelihoods. The effective implementation of these critical land reforms will ultimately facilitate the attainment of inclusive growth, boost productivity, and generate additional revenue for the government. The MEM consists of two parts: part one presents a review of recent economic developments and a macroeconomic outlook. Part two focuses on a special selected topic relevant to Malawi’s development prospects.